2014
DOI: 10.1039/c4cs00040d
|View full text |Cite
|
Sign up to set email alerts
|

The role of aromaticity in determining the molecular structure and reactivity of (endohedral metallo)fullerenes

Abstract: The encapsulation of metal clusters in endohedral metallofullerenes (EMFs) takes place in cages that in most cases are far from being the most stable isomer in the corresponding hollow fullerenes. There exist several possible explanations for the choice of the hosting cages in EMFs, although the final reasons are actually not totally well understood. Moreover, the reactivity and regioselectivity of (endohedral metallo)fullerenes have in the past decade been shown to be generally dependent on a number of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
116
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 191 publications
(316 reference statements)
4
116
0
1
Order By: Relevance
“…10 Three years later, the synthesis of the first organic derivatives of closododecaborate and closo-decaborate by the group of Muetterties 11 was the beginning of closo-borane chemistry and three-dimensional aromaticity, the type of aromaticity that characterises fullerenes. 12 The identification 13,14 of the planar triplet ground states of C5H5 + and C5Cl5 + in the late 60's provided experimental support for the existence of triplet aromaticity as predicted by Baird. 15 In 1982…”
Section: Introductionmentioning
confidence: 77%
“…10 Three years later, the synthesis of the first organic derivatives of closododecaborate and closo-decaborate by the group of Muetterties 11 was the beginning of closo-borane chemistry and three-dimensional aromaticity, the type of aromaticity that characterises fullerenes. 12 The identification 13,14 of the planar triplet ground states of C5H5 + and C5Cl5 + in the late 60's provided experimental support for the existence of triplet aromaticity as predicted by Baird. 15 In 1982…”
Section: Introductionmentioning
confidence: 77%
“…12 In 2013, with the goal of understanding the chemical origin of the stability of anionic fullerene cages, we reported an extensive study showing that, for a given C 2 n – m cage, the most stable isomers are the ones whose total aromaticity is maximized, independently of the number of APPs they have. 13,14 We formulated the maximum aromaticity criterion that gave an explanation for the isolated pentagon rule (IPR) violation in EMFs. In this study, aromaticity measurements were carried out in terms of the Additive Local Aromaticity (ALA) index.…”
mentioning
confidence: 99%
“…In this study, aromaticity measurements were carried out in terms of the Additive Local Aromaticity (ALA) index. 13,14 We used the HOMA geometric descriptor of aromaticity to reduce the computational cost. Still, the HOMA-based calculations provided aromaticity trends similar to those obtained with more reliable, but computationally more expensive electronic multicenter indices.…”
mentioning
confidence: 99%
“…16,17 Many non-IPR fullerenes have been isolated and characterized in the form of metallofullerenes. [18][19][20][21][22][23] Kinetic stability of metallofullerenes could be predicted from the min BRE for the negatively charged carbon cage. [24][25][26][27] We reported that carbon cages in all IPR and some non-IPR metallofullerenes so far isolated are kinetically stable with min BREs > -0.100 |β|.…”
Section: Introductionmentioning
confidence: 99%
“…43 In 2014, they made experimental and computational reinvestigation of recently pointed out that the originally proposed Sc 2 C 2 @C 2v (6073)-C 68 is more congruent not only with the size-shape complementality rule but also with the maximum aromaticity rule. [21][22][23] Considering that the tetraanion of C 2v (6073)-C 68 is the most aromatic isomer of the C 68 tetraanion, 21 it must possibly be the kinetically most stable isomer of C 68 4-. An X-ray single crystal structure may be required to solve these conflicting observations.…”
mentioning
confidence: 99%